Double emulsions of immiscible polymer blends stabilized by interfacially active nanoparticles. Issue 11 (5th July 2013) - Li, Qiong; Huang, Yajiang; Xi, Shuting; Yang, Qi; Li, Guangxian
<x xml:space="preserve">Abstract</x> The stability of particle‐stabilized double emulsions under flow is of great scientific and technical interest in many fields. In this work, a two‐step mixing procedure was adopted to produce double emulsions based on viscous polyisobutylene (PIB)/polydimethylsiloxane (PDMS) blends and a small amount of interfacially active hydrophobic silica nanoparticles were used to stabilize the morphology. The structures of nanoparticle‐stabilized double emulsions with varying blend ratios and nanoparticle concentrations were investigated via optical microscopy and rheology technique. It was found that increasing the nanoparticle content effectively facilitated the formation of double emulsion droplets under shear flow and improved their stabilities. Rheology results suggested that these nanoparticle‐stabilized double emulsions displayed a slower relaxation dynamics. Decreasing the concentration of dispersed phase was in favor of the generation of more stable double emulsions, possibly due to the higher particle coverage at the interface between two phases. © 2013 American Institute of Chemical Engineers AIChE J, 59: 4373–4382, 2013